ANALISIS PERBANDINGAN PRAKTIK AKUNTANSI MUDHARABAH DAN MUSYARAKAH DENGAN PSAK 105 DAN 106 DI PERBANKAN SYARIAH - Aldi Susanto; Lutfiyaumul Latifah; Padilatul Laila; Istiqomah -; Nur Alfu Laila (ICONS: Islamic Economics Journal, 2024)
Sharia banking is a financial institution that has sharia principles andapplies Islamic law in making decisions. In the form of fund distribution can beaccessed by mudharabah and musyarakah financing, in terms of the concept ofmudharabah and musharakah has the principle of trust (trust) but in practiceIslamic banks apply guarantees in their financing, this is not in accordance with theinitial principle of mudharabah and musharakah, namely the trust system. Thepurpose of this research is to find out the difference between mudharabah andmusharakah in Islamic banking and to find out the application of guarantees inIslamic banking. This type of research uses a library research approach. With theprimary data source is the book "Sharia Guarantee Law and Its Implementation inSharia Banking in Indonesia and the book Reconstruction of Guarantee Law in theMudharabah Agreement".As well as other books related to secondary data sourcescome from books, reports, journals, theses, dissertations, and other related books.The data collection technique starts from reading references, then classifying themso that they get a clear conclusion from the questions obtained so that they cananswer the problem formulation. The data analysis technique used is a comparativemethod. . The results of this study show that: the difference between mudharabahand musharakah lies in terms of understanding, legal basis, implementation inIslamic banking, capital, business management, ratio, business risk, guarantee anddispute resolution. And also that the principle of mudharabah and musharakah isthe principle of belief